El juego cognitivo como estrategia psicopedagógica para la enseñanza aprendizaje de la matemática en una niña con trastorno por déficit de atención con hiperactividad de quinto grado de la escuela de educación básica Teniente Hugo Ortiz, 2022-2023 - Delgado Alvarado, Marilyn Elizabeth (2023)
The general aim of this curriculum integration work is to apply the cognitive game as psycho-pedagogical strategy towards encourage the teaching-learning process of the Mathematics in a girl diagnosed with Attention Deficit and Hyperactivity Disorder, student of fifth grade at “Teniente Hugo Ortiz” basic education school, 2022 – 2023. It was used a qualitative approach of a descriptive type with a phenomenological design and case study method, to recollection of data was applied TEDI MATH tools and the EDAH scale and the qualitative interview and the list of achievements as techniques. As a result, the student presents TDAH of the combined type, in other words, her predominant characteristics are attention deficit and hyperactivity; it could determine that the mathematical competences that the girl show later the application of Tedi Math are very low percenters that are below 25% where the percentile places her mostly in alarm signal according to their age and year of schooling. From the interview with the teachers, it is known that they do not have the necessary training for the teaching-learning process of the Mathematics for the cases of children with TDAH, they used the experience as base to identification and application of strategies according to the students’ necessities. Through the information collected, a proposal of psycho-pedagogical strategies based on cognitive game was made to promote the teaching-learning of mathematics, obtained as a result considerable improvement in relationship to the application time; some of them achieved and a few at an initial level.